A high-performance linear generator system for wave energy conversion - Cheng, Wei Yang (Nanyang Technological University, 2023)
The world is facing a critical era where it has to decarbonise its activities while at the same time, meet the growth in energy demands. One strategy would be to grow established pathways in renewable energy while at the same time develop new and alternative pathways to it. One such pathways would be wave energy. While there have been experimental projects done in this field before, widescale adoption of wave energy has not taken off yet and many different methodologies have been trialled and proposed to harness wave energy. This project proposes to reconfigure existing linear Flux Switching Permanent Magnet (FSPM) Motor Designs as a way to harness the wave energy. Most of the energy is harnessed from the vertical component of wave motion. Further modifications are made to the generator design based on recommendations by previous studies done in this done that said to improves the performance of the FSPM Motor. The next step would be to model the design in the JMAG software which will then be followed by simulation studies. One potential application would be to deploy in Singapore’s coastal areas to harness wave energy. Alternatively, these linear generators can be deployed with countries that have higher wave energy potential and transmitted back to Singapore as part of a bilateral agreement which is what Singapore has been exploring in these past few years. While the result shows that it is not worth investing in double magnet in the linear generator, the designs with modifications recommended by the studies show substantial improvement in the performance. Further steps include verifying the experimental data with a physical prototype.